2016
DOI: 10.1038/srep24906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of conformation change and aggregation of HIV-1 Vpr13-33 on graphene oxide

Abstract: Recent experiments have reported that the fragment of viral protein R (Vpr), Vpr13-33, can assemble and change its conformation after adsorbed on graphene oxide (GO) and then reduce its cytotoxicity. This discovery is of great importance, since the mutation of Vpr13-33 can decrease the viral replication, viral load and delay the disease progression. However, the interactions between Vpr13-33 and GO at atomic level are still unclear. In this study, we performed molecular dynamics simulation to investigate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The action of GO was investigated more explicitly by representing the substrate using the Lerf-Klinowski model (Lerf et al, 1998 ), which describes the behavior of a standard oxidation process. Using this approach, two paradigmatic articles (Sun et al, 2014 ; Zeng et al, 2016 ) demonstrated that GO displays an enhanced adsorption of the attached protein. Firstly, in Sun et al ( 2014 ), an atomistic description of the inhibitory action of GO on the activity of α-chymotrypsin (ChT), has been provided.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…The action of GO was investigated more explicitly by representing the substrate using the Lerf-Klinowski model (Lerf et al, 1998 ), which describes the behavior of a standard oxidation process. Using this approach, two paradigmatic articles (Sun et al, 2014 ; Zeng et al, 2016 ) demonstrated that GO displays an enhanced adsorption of the attached protein. Firstly, in Sun et al ( 2014 ), an atomistic description of the inhibitory action of GO on the activity of α-chymotrypsin (ChT), has been provided.…”
Section: Computational Modeling and Simulations Of Graphene-interactimentioning
confidence: 99%
“…For example, an HIV-1 regulatory protein undergoes α-helix to β-sheet structural changes upon graphene association [18]. Similarly, VPR 13-33 adsorption on the graphene oxide surface caused the loss of secondary structure [42]. Strong dispersion interactions of the solvent-exposed basic residues and graphene can provide the major driving force [41] for protein structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent-accessible surface area was calculated with the Gromacs library [ 36]. The contacting surface area can be then calculated using the following formula: CSA = (SASA Peptide(s) + SASA DNA -SASA Peptide(s)-DNA)/2 [ 37]. Initially, the CSA was close to zero due to the distance between peptides and DNA.…”
Section: Contacting Surface Areamentioning
confidence: 99%